STUDI PERBANDINGAN PENGGUNAAN PCU GIRDER DAN PCI GIRDER PADA STRUKTUR ATAS JEMBATAN JURANG GEMPAL, WONOGIRI - Putra, Bastya Pratama; Muntafi, Yunalia; Suharyatmo, Suharyatmo (Teknisia, 2018)
The Bridge is one of the infrastructure buildings that support social, economic and industrial growth of a region. Jurang Gempal Bridge in Wonogiri is the main highway access that connects the Solo-Wonogiri Road. The main material of that bridge is steel which has corrosive prone nature so that need a routine maintenance. In contrast to steel, concrete material is easier to maintain and better to reduce shocks. Therefore, this research will be use concrete material that is PCU Girder and PCI Girder on the upper structure of the bridge.The research aims to compare the results of the design related to required total Girder area, number of tendons and reinforcement of the bridge designed with PCU Girder and PCI Girder from the Binamarga Office of Central Java. Research begins by surveying the location of the bridge, collecting the data, then designing and comparing the bridge upper structure design with both the PCU Girder and PCI Girder. The research shows that the design of PCU Girder bridge requires less girder than the PCI Girder, but the total area of the Girder is 36% greater than PCI Girder. Likewise, the need of tendons, moment, and shear reinforcement of PCU Girder bridge is more than the PCI Girder bridge.